Heterogeneous Conductance‐Based Locally Shape‐Morphable Soft Electrothermal Actuator. Issue 2 (11th December 2019) - Ahn, Junseong; Jeong, Yongrok; Zhao, Zhi‐Jun; Hwang, Soonhyoung; Kim, Kyuyoung; Ko, Jiwoo; Jeon, Sohee; Park, Jaeho; Kang, Hyeokjung; Jeong, Jun‐Ho; Park, Inkyu
Abstract: The development of soft electrothermal actuators (ETAs) that can be designed in arbitrary shapes and can easily handle soft objects has recently attracted much attention. However, the existing ETAs cannot be locally designed with a single substrate geometry, which places certain limitations on their applications. In addition, some limited materials (e.g., highly aligned carbon nanotubes) are used as heating layers for improving actuation controllability, which results in a high driving voltage, thus limiting the diversity and utility of ETAs. Herein, a novel method for a heterogeneous conductance‐based locally shape‐morphable electrothermal actuator (HC‐ETA) is suggested, revealing that conductance programming allows control of the heat distribution in ETAs. Thus, by controlling the actuator heat distribution, the designed actuation motion can be implemented. Furthermore, Ag nanowire/carbon nanotube composites are used as conductive nanomaterials for a heating layer to realize a low‐driving‐voltage actuator. Additionally, combining a porous fabric substrate with a bipolymer actuator structure allows mechanical interlocking and the chemical bonding between actuator multilayers, resulting in significantly enhanced mechanical durability. Finally, the utility of the proposed actuator and the corresponding design method is successfully demonstrated by fabricating a biomimetic self‐walking robot and an object lifting soft robot for vacuum chamber applications. Abstract : Fabricating locally shape‐morphable soft electrothermal actuator (ETA) remains a challenging task. Here a novel method of ETA design is described, revealing that controlling heterogeneous conductance of ETA facilitates the fabrication of locally shape‐morphable ETA. Moreover, by employing the unique characteristic of a fabric substrate to achieve thick nanomaterial coating and strong bonding simultaneously, performance of the actuator shows dramatic enhancement.